Métodos de piano e suas relações na formação de professores do instrumento - Dambros, Gabriela da Silva (My University, 2019)
The present academic work consists of exposing a study of piano methods. The objective of this work is to investigate the influences that the teaching methodologies of piano received in the teaching practice of instrument teachers. A brief history about the trajectory of musical education from antiquity to the twentieth is presented. Piano methods, based on Keith Swanwick's C(L)A(S)P model, will be analyzed. Through the application of qualitative exploratory research, the respondents answers were analyzed based in the theories studied about piano teacher practice. The results show that there is influence in the relation of methods choices of the teachers to their students according to the methods used in pianistic formation of these teachers as students. It was also found that the interviewees seek new possibilities of methodologies to improve their teaching actions according to the difficulties and specific needs of each students. It was concluded that the knowledge about different methods and their influences contribute to provide a theoretical and practical expansion to obtain an understanding of method choice and repertoire to be used in piano teaching (sic).
O presente trabalho consiste em expor um estudo sobre métodos de piano. O objetivo deste trabalho é investigar as influências que as metodologias de ensino de piano auferem na prática docente de professores do instrumento. Um breve histórico sobre a trajetória da educação musical desde a antiguidade até o século XX é apresentado. Métodos de piano foram analisados baseados no modelo C(L)A(S)P, de Keith Swanwick. Através da aplicação de uma pesquisa exploratória qualitativa, as respostas dos entrevistados foram analisadas à luz das teorias estudadas sobre a prática docente ao piano. Os resultados demonstram que há influência na relação da escolha dos métodos dos professores para seus alunos em função dos métodos utilizados na formação pianística desses professores enquanto alunos. Constatou-se também que os entrevistados buscam novas possibilidades de metodologias para melhorar suas ações docentes de acordo com as dificuldade e necessidades específicas de cada aluno. Concluiu-se que os conhecimentos sobre diferentes métodos e suas influências contribuem para proporcionar uma expansão teórica e prática para a obtenção de um entendimento da escolha do método e repertório a ser utilizado no ensino do piano (sic).
Keywords: Música; Piano - Métodos; Piano - Instrução e estudo